Attitudes of parents and staff towards medical students on the paediatric wards. - Roche, Edna; Gadelsayed, Montasser; Meehan, Judith (My University, 2014)
This study investigates attitudes of parents and staff to medical students on paediatric wards in a Dublin teaching hospital. We invited 100 parents of patients and 30 staff involved in the care of children on the paediatric wards to participate. The majority of parents agreed or strongly agreed that they would be happy for a student to interview them (n= 87; (87%)), interview their child (80%) or examine their child (74%). Of 30 staff, 12 (40%) staff agreed that the presence of medical students on the ward increased their job satisfaction, 13 (43%) agreed or strongly agreed that medical student presence encouraged them to keep up to date with recent medical developments and 6 (20%) felt that it increased the quality of patient care. Attitudes of both parents and staff to medical students on paediatric wards are positive with both emphasising the need for professional behaviour.
PUBLISHED
Keywords: Medical students